2021
DOI: 10.3389/fpubh.2021.675403
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Its Influence on the Health of Preschool Children in Hangzhou

Abstract: Objective: Vitamin D deficiency and insufficiency in children are global public health problems. However, few studies have focused on vitamin D status in healthy preschool children, especially in Asia. This study aimed to investigate vitamin D status and host-related factors in healthy preschool children in Hangzhou to analyze the impact of low vitamin D levels (<30 ng/mL) on health outcomes (obesity, early childhood caries, and respiratory tract infections).Methods: A total of 1,510 healthy children ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
(44 reference statements)
3
13
1
3
Order By: Relevance
“…Our finding adds to the growing literature pointing to an association between low 25(OH)D and caries in children [4,10,12,21,22]. While most of these studies are crosssectional in design, there is emerging evidence from prospective studies that also indicate an inverse relationship [10,22,23].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our finding adds to the growing literature pointing to an association between low 25(OH)D and caries in children [4,10,12,21,22]. While most of these studies are crosssectional in design, there is emerging evidence from prospective studies that also indicate an inverse relationship [10,22,23].…”
Section: Discussionsupporting
confidence: 57%
“…This review also suggested that low vitamin D levels should be considered as a potential risk factor for caries in children [5]. A recent Chinese study reported that children with optimal 25(OH)D levels had a significantly lower prevalence of ECC [21], while a small study from Iraq reported significantly higher 25(OH)D levels among caries-free preschool children [26]. However, another study revealed a statistically weak relationship between 25(OH)D status in early childhood and caries in primary teeth in children who were 6 years old [23].…”
Section: Discussionmentioning
confidence: 99%
“…Serum 25(OH)D levels in children in the Zigong area did not differ statistically significantly between sex, consistent with Xiao Long-necked [ 19 ] and others, and were lower in winter and spring and higher in summer and autumn, due to less sunlight and lower UV exposure and reduced skin synthesis in winter and spring than in summer and autumn. 25-hydroxyvitamin D levels are highest in children under 1 year of age and their levels decrease with increasing age, as also observed in Hangzhou, China [ 20 ]. The reason for this may be that children under the age of 1 year are mainly fed on breast milk or formula.…”
Section: Discussionmentioning
confidence: 67%
“…Although there is limited evidence of a correlation between vitamin levels and gender, girls have an overall 32% increased risk of vitamin deficiency compared with boys 30 . Similar studies from South Africa, China, and Ecuador have not found sex‐related differences in vitamin levels 30–32 . Studies have shown that dietary habits and diet structure have a significant impact on metabolism and the status of essential nutrients 33 .…”
Section: Discussionmentioning
confidence: 99%
“… 30 Similar studies from South Africa, China, and Ecuador have not found sex‐related differences in vitamin levels. 30 , 31 , 32 Studies have shown that dietary habits and diet structure have a significant impact on metabolism and the status of essential nutrients. 33 Both Vit A and D firstly increased, but then decreased with age, while Vit E exhibited the opposite effect.…”
Section: Discussionmentioning
confidence: 99%